Digital Transformation as a Reinforcement of Competitive Advantage and Resilience of Highland Tourism Villages in Central Java - Ahmad Mansur; Tonny Hendratono; Sugiarto Sugiarto (Akademi Kesejahteraan Sosial Ibu Kartini Semarang, 2026)
This study aims to analyze the role of digital transformation in strengthening competitive advantage and resilience of highland tourism villages in Central Java. Highland tourism villages face increasing competition, environmental vulnerability, and market uncertainty, requiring adaptive and innovation-driven strategies. Digital transformation is considered a strategic instrument to enhance destination competitiveness, expand market access, and improve institutional resilience. This research employs a quantitative approach using Structural Equation Modeling (SEM-PLS) to examine the relationships among digital transformation, competitive advantage, and tourism village resilience. The study was conducted in selected highland tourism villages in Central Java, including [insert village names if needed]. Data were collected through structured questionnaires distributed to tourism village managers, local stakeholders, and community representatives. The findings indicate that digital transformation has a significant positive effect on competitive advantage and resilience. Furthermore, competitive advantage partially mediates the relationship between digital transformation and tourism village resilience. These results suggest that digital adoption, digital marketing integration, and digital governance practices are critical in strengthening sustainable tourism development in highland areas. The study contributes to the literature on digital tourism transformation and provides managerial implications for policymakers and tourism village managers in developing adaptive and resilient tourism ecosystems.